Evaluation of aqueous humor and serum cortistatin levels in diabetic patients with and without diabetic retinopathy. Issue 2 (March 2021) - Balbaba, Mehmet; Ulaş, Fatih; Erdağ, Murat; Yıldırım, Hakan; Çeliker, Ülkü; Aydın, Süleyman
Purpose: To evaluate the aqueous humor and serum cortistatin levels in diabetic patients with and without diabetic retinopathy and its relationship with various metabolic markers that have been reported to be associated with diabetes mellitus. Methods: The current study included 20 diabetes mellitus patients with diabetic retinopathy, 20 diabetes mellitus patients without diabetic retinopathy, and 20 healthy control subjects with the same sex and age characteristics. Aqueous humor and serum cortistatin, fasting blood glucose, hemoglobinA1c, 25-hydroxyvitamin D levels, blood lipid profiles, and body mass index were measured in all subjects. Results: In diabetic patients with and without diabetic retinopathy and in healthy control subjects, the mean aqueous humor cortistatin levels were 25.55 ± 2.03, 27.71 ± 2.01, and 32.76 ± 3.43 ng/mL, respectively. Likewise, the mean serum cortistatin levels were 6.16 ± 1.08, 6.57 ± 1.00, and 7.56 ± 1.51 ng/mL, respectively. Aqueous humor cortistatin levels were decreased in diabetic patients with and without diabetic retinopathy when compared to healthy controls ( p < 0.001). Although aqueous humor cortistatin levels tended to be reduced in diabetic patients with diabetic retinopathy, the difference was not statistically significant between diabetic patients with and without diabetic retinopathy ( p = 0.147). Serum cortistatin levels were not statistically significant between diabetic patients with and without diabetic retinopathy and healthy control subjects ( p = 0.166). Body mass index, fasting blood glucose, and hemoglobinA1c levels were significantly different between the groups ( p < 0.05 for all parameters tested). Conclusion: Aqueous humor cortistatin levels were decreased in diabetic patients with and without diabetic retinopathy. The results suggest that a local decrease in the amount of cortistatin may play a role in the pathogenesis of diabetic retinopathy.